Aplikasi Bokashi Ampas Tahu dan Poc Sabut Kelapa Muda Terhadap Produksi Melon Madu (Cucumis melo L.) - Bhayata, Afif; Titisari, Prima Wahyu (Universitas Teuku Umar, 2024)
This study aimed to determine the interaction effect and the main effect of tofu dregs bokashi and Liquid Organic Fertilizer (LOF) from young coconut fiber on the growth and production of melon plants. This research has been carried out at the Experimental Garden of the Faculty of Agriculture, Riau Islamic University, Pekanbaru City. The study lasted four months, starting in February and ending in May 2022. This study used a factorial, completely randomized design with two factors. The first factor was the dose of bokashi tofu dregs, consisting of 4 levels, namely 0 kg/plot, 1.5 kg/plot, 3 kg/plot, and 4.5 kg/plot. The second factor was the dose of young coconut coir POC, which consisted of 4 levels, namely 0 ml/plant, 100 ml/plant, 200 ml/plant, and 300 ml/plant. So that there were 16 treatment combinations with three replications, 48 experimental units were obtained. Each experimental unit consisted of 4 plants, and 2 of them were sampled, so the total number of plants was 192 plants. Parameters observed were flowering age, harvest age, fruit weight per fruit, fruit weight per plant, fruit girth, root volume, sweetness level, and flesh thickness. The results showed that there was a significant interaction between the treatment of bokashi tofu dregs and POC of young coconut coir on the observation of flowering age, harvest age, fruit weight per fruit, fruit weight per plant, and fruit sweetness level. The best treatments were tofu dregs bokashi at a dose of 4.5 kg/plot and POC young coconut husks at a dose of 300 ml/plant. The main effect of tofu dregs bokashi was significant on all observation parameters. The best treatment for tofu dregs bokashi was 4.5 kg/plot. The main impact of young coconut coir POC is substantial on all observation parameters. The best treatment for young coconut coir POC is at a dose of 300 ml/plant